Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation Pada Mata Pelajaran Otomatisasi Tata Kelola Kepegawaian Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa - Henik Triana; Brillian Rosy (Universitas Negeri Surabaya, 2020)
This study aims to determine the effect of cooperative learning models type group investigation on critical thinking ability and student learning outcomes in class XI OTKP SMK Negeri 2 Tuban. Type of experimental reseach with quasi experimental design. The reseach sample is class XI OTKP 1 dan 2. Data collection methods using tests, documentation, interview and observation. Research instrument used in the cognitive and psychomotor domain. Data analisis use homogeneity test, normality test, gain score test, and hypothesis test. The ability to think critically in the hypothesis test gets the result of tvalue > ttable (5,585>1,994) the significance level is 0,000<0,05. The hypothesis test result of learning outcomes show value tvalue > ttable (4,493>1,994) significance level is 0,000 < 0,05. T-test gain score analysis obtained the results of tvalue > ttable (5,750>1,994) significance level is 0,000<0,05. Based on these results it can be interpreted that H1 ia accepted. Can be concluded that the cooperative learning model type group investigation influences critical thinking ability and student learning outcomes.